A Synchronized Analysis of Norms and Structural Barriers to Enforcement of Law Number 12 of 2022 concerning Sexual Violence - Muhammad Ismail Sholeh; Putri Maha Dewi; Zia Aftab (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
This study aims to analyse the criminalisation of sexual violence offences from the perspective of Law No. 12 of 2022 on Sexual Violence Offences (the Sexual Violence Offences Act) as a form of reform of national criminal law, and to assess its alignment with the principles of modern criminal law. The background to this research is based on the limitations of the old Criminal Code (KUHP), which has been unable to comprehensively accommodate various forms of sexual violence, particularly contemporary forms such as non-physical sexual harassment, sexual exploitation, forced marriage, and electronic-based sexual violence. This study employs a normative legal methodology, utilising legislative, conceptual and analytical approaches through a literature review of primary, secondary and tertiary legal sources. The results of the study indicate that the TPKS Act constitutes a progressive criminalisation policy that broadens the scope of sexual violence offences, strengthens victim protection through restitution, rehabilitation, and support, and shifts the orientation of criminal law from the protection of public morality towards the protection of human rights and the dignity of victims. From a normative perspective, the TPKS Act has fulfilled the principles of legality, proportionality and victim-oriented criminal law, although the principle of ultimum remedium has shifted towards premium remedium due to the serious nature of the offences. This study also found that the main obstacles lie in implementation, particularly regarding the capacity of law enforcement officials, the legal culture of society, and the effectiveness of implementing regulations. Consequently, the success of the TPKS Law as an instrument of criminal law reform is largely determined by the alignment of legal norms and the optimisation of victim protection measures.